Superimposed type 2 segmental atopic dermatitis: case series and review of the literature. (1st September 2022) - Bar‐Ilan, Efrat; Mashiah, Jacob; Alkalay, Ronen; Ingber, Arieh; Zahavi, Keren Or; Bar, Jonathan; Zeeli, Tal; Gat, Andrea; Samuelov, Liat; Sprecher, Eli; Goldberg, Ilan
Abstract: Generalized acquired dermatoses can seldom manifest more prominently or exclusively along the lines of Blaschko. Six individuals with segmental atopic dermatitis (AD) have been reported to date. We present three additional cases of segmental cutaneous manifestations superimposed on generalized AD, and review the relevant literature. Abstract : Generalized acquired dermatoses can seldom manifest more prominently or exclusively along the lines of Blaschko. Six individuals with segmental atopic dermatitis (AD) have been reported to date. We present here three additional cases of segmental AD that support the existence of this rare and often treatment‐resistant form of AD.